Hello,

there are a lot of different ways to get the 4 points. In this case it would be the best to do the calculations like this:

(X-4)^2 + (Y-3)^2 = 4 ===> (Y-3)^2 = 4 - (X-4)^2

(X-4)^2/ 9 + (Y-3)^2/ 1 = 1 ===> (Y-3)^2 = 1 - (X-4)^2/ 9 Therefore:

4 - (X-4)^2 = 1 - (X-4)^2/ 9 ===> 3 = (X-4)^2 - (X-4)^2/ 9

3 = (8/9)*(X-4)^2 ===> (27/8) = (X-4)^2 (******)

x = 4 ± (3/4)*√(6)

Use this (*****) result to calculate y:

(Y-3)^2 = 4 - (X-4)^2 ===> (Y-3)^2 = 4 - (27/8) = (5/8)

y = 3 ± (1/4)*√(10)

The 4 points are:

(4 + (3/4)*√(6), 3 + (1/4)*√(10)); (4 + (3/4)*√(6), 3 - (1/4)*√(10)); (4 - (3/4)*√(6), 3 - (1/4)*√(10)); (4 - (3/4)*√(6), 3 - (1/4)*√(10))

EB